Plan de Negocios para la implementación de una empresa comercializadora de materiales eléctricos en el sur de Quito. - Sopalo Moposita, Juan Carlos (2023)
Electrical energy as a permanent and necessary resource for the development of different human activities requires different electrical and electronic elements, for which the present research project aims to analyze the feasibility for the implementation of a materials trading company. residential electrical and electronic security in the parish of Cutuglagua, belonging to the Mejía canton of the province of Pichincha. Through exploratory research, data was collected from 187 families in the sector through the survey tool, where the needs, expectations, supply and unsatisfied demand of the population were identified. For the development of the business plan, the CANVAS canvas is considered, for this purpose the 9 blocks are clearly and precisely illustrated. The business name of the marketer will be represented under the name of SMELECTRICS whose penetration and positioning in the market was carried out through the Marketing strategy of the 4p's, in the same line is to provide good customer service accompanied by technical advice by our qualified staff.